The Effect of Eye Movement Desensitization and Reprocessing (EMDR) on the severity of suicidal thoughts in patients with major depressive disorder: a randomized controlled trial - Fereidouni Z (Dove Medical Press, 2019)
Zhila Fereidouni,1 Mohammad Behnammoghadam,2 Abdolhadi Jahanfar,1 Azizallah Dehghan31Department of Medical Surgical Nursing, Nursing School, Fasa University of Medical Sciences, Fasa, Iran; 2Department of Critical Care Nursing, Yasuj University of Medical Sciences, Yasuj, Iran; 3Noncommunicable Diseases Research Center, Fasa University of Medical Sciences, Fasa, IranCorrespondence: Abdolhadi JahanfarDepartment of Medical Surgical Nursing, Nursing School, Fasa University of Medical Sciences, Fasa Ibn Sina Square, PO Box 7461686688, Fasa, IranEmail jahanfarhadi91@gmail.comMohammad BehnammoghadamDepartment of Critical Care Nursing, Yasuj University of Medical Sciences, Yasuj, IranEmail mbehnam1363@gmail.comObjective: Depression is a major risk factor for suicide and more than 90% of people who attempt suicide suffer from depression. The present study aimed to investigate the effect of eye movement desensitization and reprocessing (EMDR) therapy on the severity of suicidal thoughts in patients with major depressive disorder.Study design: Randomized Clinical Trial.Methods: This clinical trial was performed on 70 people with major depressive disorder who exhibited suicidal thoughts. The patients were selected via convenience sampling and were randomly divided into control (n=35) and experimental (n=35) groups. EMDR was performed individually in the experimental group for 45–90 min, 3 days per week, on alternate days, for 3 weeks (9 sessions in total), whereas the controls group received routine treatment without intervention. Both groups completed the Beck Scale for Suicide Ideation (BSSI) at pre- and post-test. The obtained data were analyzed with descriptive and inferential statistics using SPSS 22 (α=0.05).Results: Mean BSSI score for the experimental group was reduced significantly at post-test (11.11±4.15) compared to pre-test (26.48±5.74) (p<0.001). Although the control group’s mean BSSI score was also reduced at post-test (24.93±4.42) compared to pre-test (26.68±5.05), this difference was not statistically significant (p>0.05).Conclusion: EMDR therapy has been shown in this study to reduce the severity of suicidal feelings. Therefore, it can be recommended as an alternative treatment method for reducing the severity of suicidal thoughts in patients with major depressive disorder.Keywords: major depressive disorder, suicidal thoughts, eye movement desensitization and reprocessing